Pengembangan Kurikulum Muatan Lokal Berbasis Budaya Ungkapan Prolog Bahasa Melayu Jambi sebagai Mata Kuliah Ciri Kedaerahan pada Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Jambi - Andiopenta Purba (Universitas Batanghari Jambi, 2023)
Jambi Malay is rich in expressions that can be used as teaching materials in the development of local content curriculum in the field of culture. Things related to this expression include; (1) the form of expression in Jambi Malay can be in the form of phrases, clauses, and sentences. (2) the meaning contained in Jambi Malay expressions can be in the form of grammatical, connotative and implied meanings, and (3) the use of Jambi Malay expressions is as satire, suggestion, advice, and as a rule norm that must be obeyed and implemented. This expression is always used as a prologue when speaking in the realm of family, custom, government and state ceremonies. All of these expressions were developed into teaching materials in the development of local content curricula in formal schools in Jambi province. In determining local content subjects, there are several steps that can be taken, including; (1) identify regional conditions and needs; (2) determine the function and composition or composition of local content; (3) determining local content study materials; (4) determining local content materials; and (5) develop competency standards and basic competencies and learning syllabus. These five steps will of course be based on the form, meaning, and function of the various prologue expressions of Jambi Malay.